The influence of knowledge and work experience on employee performance with work motivation as a moderating variable - David Ahmad Yani; Sri Suyarti (Enrichment : Journal of Management, 2023)
The purpose of this research is to identify the role that work motivation plays in mediating the relationship between employee knowledge and experience and job performance. This study employed a quantitative research design for its investigation. Forty participants, all of whom worked for a construction services firm, were interviewed for this study. Probability sampling using the quota sampling approach was employed in this investigation. Two independent (X1 and X2) variables, one dependent (Y), and one moderating (M) variable are involved in this analysis. Validity, reliability, model, and hypothesis testing are all components of this investigation. Moderate regression analysis is employed for the analysis (MRA). Employee performance (Y) and work motivation (Z) serve as moderators between the independent variables of knowledge (X1) and work experience (X2). This is what one sees in the data. Employee performance (Y) is influenced by knowledge (X1) to the tune of 79.5%. The level of influence of job experience (X2) on worker performance (Y) is 77.8%. Knowledge (X1) has an effect on worker output (Y), with job motivation serving as a moderating variable (83% of the total influence).